Recapitulating epithelial tumor microenvironment in vitro using three dimensional tri-culture of human epithelial, endothelial, and mesenchymal cells. Issue 1 (December 2016) - Lamichhane, Surya; Arya, Neha; Kohler, Esther; Xiang, Shengnan; Christensen, Jon; Shastri, V.
Abstract Background Three-dimensional (3-D) cultures of cancer cells can potentially bridge the gap between 2-D drug screening and in vivo xenografts. The objective of this study was to characterize the cellular and extracellular matrix characteristics of spheroids composed of human lung epithelial cells (epi), pulmonary vascular endothelial (endo) cells, and human marrow-derived mesenchymal stems cells (MSCs). Methods Spheroids composed of epi/endo/MSCs, termed herein as synthetic tumor microenvironment mimics (STEMs), were prepared by the hanging drop method. Cellular composition and distribution in the STEMs was characterized using fluorescence microscopy. Induction of reactive oxygen species and upregulation of efflux transporters was quantified using fluorometry and PCR, respectively, and phenotypic markers were qualitatively assessed using immunohistochemistry. Results STEMs exhibited three unique characteristics not captured in other spheroid cultures namely, the presence of a spheroid core devoid of epithelial cells and primarily composed of MSCs, a small viable population of endothelial cells hypothesized to be closely associated with MSCs within the hypoxic core, and discrete regions with high expression for vimentin and cytokeratin-18, whose co-expression is co-related with enhanced metastasis. Although cells within STEMs show elevated levels of reactive oxygen species and mRNA for ABC-B1, an efflux transporter associated with drug resistance, they exhibited only modest resistance to paclitaxel and gemcitabine in comparison to 2-D tri-cultures. Conclusions The epi/endo/MSC spheroid model described herein offers a promising platform for understanding tumor biology and drug testing in vitro.